How is coaches` social identity leadership related to mental health in elite athletes? The mediating role of satisfaction with performance - López de Subijana, C.; Pons, J.; Mallett, C. J. (Journal of Sports Sciences, 2024)
It has been found that the way high-performance coaches lead influences both athletes` performance and mental health. However, limited research exists on the Social Identity Approach to leadership in elite sports, despite growing interest in coaching science regarding interpersonal behaviours and leadership. This study investigates the empirical links between coaches` leadership, sport performance and mental health from a social identity approach. One hundred and forty-five elite athletes (Mage = 20.6 years; SD = 4.1; 62% women, 38% men) answered questionnaires measuring coaches` social identity leadership, sport performance satisfaction and mental health. The overall structural equation model (SEM) accounted for 36% and 19% of the variances in athletes` mental health and mental illness dimensions, respectively. There was a positive association between perceived coaches` social identity leadership and sport performance satisfaction, explaining 10% of its variance. Coaches` social identity leadership predicted athletes` mental health but not mental illness. Sport performance satisfaction positively influenced mental health and negatively impacted mental illness. Fostering a sense of "we" and "us" within elite sport training groups is instrumental in promoting sport performance satisfaction and, consequently, enhancing the mental health of athletes. Coaching educational courses may benefit from social identity leadership in interpersonal behaviours.